Tailored Teaching for Specialized (Para-)medical Students - Experience From Incorporating a Relevant Genetic Disease Throughout a Course of Molecular Cell Biology - Ton Schoenmaker; Dongmei Deng; Teun J. de Vries (Frontiers Media S.A., 2020)
Worldwide, a mandatory course in Molecular Cell Biology is often part of the (para-) medical curricula. Student audiences are regularly not receptive to such relatively theoretical courses and teachers often struggle to convey the necessary information. Here, positive experience is shared on rigorously embedding a genetic disease that severely affects the movement apparatus, fibrodysplasia ossificans progressiva (FOP), in all aspects of a course for an international group of Research Master Human Movement Sciences students. Various molecular cell biological aspects of FOP were systematically implemented in the course, covering genetics, the biochemical consequences of the mutation, signaling pathways that affect bone formation and lectures on how to clone the mutation or cure the mutation. Students were invited to critically think about how to use the theories learned in the course to analyze a research paper. During the practical part of the course, students assisted in novel, cutting edge research on FOP patient derived or control cells. Research findings were reported in a research paper format. By building a Molecular Cell Biology course around an appealing disease, we managed to increase the general motivation of the students for the course as reflected in two specific questions of the course evaluations (p < 0.05). It convincingly taught the relevance of a course of Molecular Cell Biology to students with a primary background in biomechanics and physiotherapy for their paramedical professional life. This approach of embedding an audience-tailored human disease with a known genetic cause into a course can be implemented to many medical curriculum related courses and will increase students' perception of the relevance of a course.